Morphology of the Testis in Leopard (Panthera pardus fusca) - Rajani, C.V. (Indian Journal of Veterinary Anatomy, 2020)
The study was conducted on testis collected from two adult leopards. Testis had a dense capsule and a centrally placed mediastinum testis. Seminiferous epithelium contained Sertoli cells and various developmental stages of spermatogenic cells. The shape, size and position of cells along with the staining character and distribution of chromatids were the criteria used to distinguish the various cell types. Rete testis was lined by simple Cuboidal to simple squamous epithelium. The study revealed the gross and histological features of epididymis in leopard and the data form basis for understanding other pathological conditions.